Design and Application of a Near Field Microwave Antenna for the Spin Control of Nitrogen-Vacancy Centers - 杨丽丽 刘刚钦 潘新宇 陈东敏 (Chinese physics letters, 2010)
Controlled manipulation of the electron spin by means of a microwave field is investigated. The near magnetic field generated by a copper wire antenna is measured experimentally and simulated theoretically, and the optimum antenna length and position are obtained. By measuring the change in the fluorescence of nitrogen-vacancy （N-V） centers in diamond after excitation with a 532 nm continuous wave laser at room temperature, it is verified that the spin of the N-V center can be effectively controlled by the microwave field.